Cash Flow Forecasting: Best Practices for Managing Treasury Operations - qizi, Shаmsitdinоvа Xоnzоdа Mаrdоnbеk (Journal of Research in Innovative Teaching and Inclusive Learning, 2024)
Effective cash flow forecasting is critical for managing treasury operations, ensuring liquidity, and supporting strategic financial planning. This paper explores best practices in cash flow forecasting, emphasizing their role in enhancing treasury management. By analyzing various methodologies, tools, and techniques, the study provides a comprehensive guide for organizations aiming to improve their cash flow forecasting capabilities. Empirical evidence from case studies and surveys illustrates the impact of these best practices on organizational performance and financial stability.